2021
DOI: 10.1126/scitranslmed.abd8995
|View full text |Cite
|
Sign up to set email alerts
|

scRNA-seq of human vitiligo reveals complex networks of subclinical immune activation and a role for CCR5 in T reg function

Abstract: scRNA-seq of human vitiligo samples reveals complex autoimmune networks, including a role for CCR5 in T reg function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 72 publications
2
49
0
Order By: Relevance
“…To better understand the initiation and progression of vitiligo, Gellatly et al employed suction blistering and scRNA‐seq on affected and unaffected skin in vitiligo patients along with healthy individuals’ skin 66 …”
Section: Applications In Skin Researchmentioning
confidence: 99%
“…To better understand the initiation and progression of vitiligo, Gellatly et al employed suction blistering and scRNA‐seq on affected and unaffected skin in vitiligo patients along with healthy individuals’ skin 66 …”
Section: Applications In Skin Researchmentioning
confidence: 99%
“…For example, ligand–receptor analysis revealed the regulatory potential from resident epidermal/mesenchymal cells to dendritic cells during psoriasis [ 59 ]. More recently, cell–cell communication analysis of scRNA-seq of human vitiligo revealed that cell type–specific signaling programs and CCR5–CCL5 signaling was critical to effector CD8+ T cell and Treg function in vitiligo, implying the potential role of chemokine circuits in driving lymphocyte localization [ 60 ].…”
Section: Biological Insights Gained By Cell–cell Communication Analys...mentioning
confidence: 99%
“…The expression of immune profile including transcription factor T-beta, TBX21 (T-Box Transcription Factor 21), CXCR3, and CCR5 (C-C Motif Chemokine Receptor 5) in T reg is believed to support the formation of resident memory T cells ( Ferreira et al, 2020 ). Current studies based on single-cell RNA sequencing of human vitiligo reveals that CCL5-CCR5 cytokine signaling serve as a chemokine circuit between effector CD8 + T cells and T reg cells ( Gellatly et al, 2021 ). Therefore, modulating the immune response is considered as a therapeutic target for the treatment of vitiligo.…”
Section: Pathogenesis Of Immunity In Vitiligomentioning
confidence: 99%